(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
Translation is considered as a linguistic ¸literary¸ and cultural process. Through translation¸ the great parts cultural features are transmitted from the original text to the translated one. The translator tries to cover some gaps by depending on adaptation via using notes ¸for example, and other techniques. In this article, we suggest the techniques used by GALLAND to translate the work “one thousand and one nights” for covering gaps and transmitting ideas. Keywords: translation, culture, adaptation, omission, addition, equivalent, substitution.